Two new species of Ceropales (Ceropales) Latreille (Hymenoptera, Pompilidae), with a key to species from China - Lu, Hai-Xia; Bashir, Nawaz Haider; Li, Qiang; Ma, Li (Zootaxa, 2019)
Two new species in the Ceropales helvetica species-group are described: Ceropales (Ceropales) longisulcata Lu & Li, sp. nov. from Inner Mongolia, China and Ceropales (Ceropales) yunnanensis Lu & Li, sp. nov. from Yunnan, China. A key to the species of Ceropales (C.) from China is provided.